Giant Temporal Lobe Cholesteatoma - Ibrahim, Sabri (Open Access Macedonian Journal of Medical Sciences, 2020)
INTRODUCTION: Intracranial cholesteatoma is uncommon about 0.2–1.8% of all tumor lesions, composed of desquamated debris lined by keratinized squamous epithelium, divided into congenital and acquired. Congenital cholesteatoma occurred early, while acquired cholesteatoma associated with otitis media. CASE REPORT: Case-1 18-year-old male with 2 years recurrent seizures, 2 times per week, lasted 1–3 min, headache, left-sided hemiparesis, and right-sided hearing impairment at 10 years from chronic suppurative otitis media at 5 years old. Brain magnetic resonance imaging (MRI) examination revealed a mass on the right temporal base measured 5.8 × 6.2 mm. Surgery was done, histopathology revealed cholesteatoma. Two weeks post-operative, normal motoric with no seizures. Case-2 45-year-old male, complaining motor aphasia for 2 years, hemiparesis for 1 year, seizures in a month, headache, and impairment of left-sided hearing. MRI examination revealed a large mass at the left temporal. Surgery was done, histopathology revealed cholesteatoma. Five days post-operative, the patient talked in slow speech and normal function achieved a month after. Cholesteatoma is a rare benign lesion, described as misplaced skin, divided into intracranial, the external auditory canal and otitis media, found commonly at the frontal or temporal bone. Infection of Streptococcus spp., MRSA, and Pseudomonas aeruginosa is common. In our case, no positive culture was found. Commonly has good surgical prognosis, neurological deficit, otorrhea, tumor recurrence, and infection was not found on our yearly follow-up. CONCLUSION: Cholesteatoma, as a non-invasive lesion compared to other intradural lesions, presents with atypical symptoms, signs, and images.